Persistence of Campylobacter spp. in Poultry Flocks after Disinfection, Virulence, and Antimicrobial Resistance Traits of Recovered Isolates - Manel Gharbi; Awatef Béjaoui; Safa Hamrouni; Amel Arfaoui; Abderrazak Maaroufi (MDPI AG, 2023)
To investigate the persistence risk of Campylobacter spp. in poultry farms, and to study the virulence and antimicrobial resistance characteristics in the recovered strains, we collected 362 samples from breeding hen flocks, before and after disinfection. The virulence factors were investigated by targeting the genes; flaA, cadF, racR, virB11, pldA, dnaJ, cdtA, cdtB, cdtC, ciaB, wlaN, cgtB, and ceuE by PCR. Antimicrobial susceptibility was tested and genes encoding antibiotic resistance were investigated by PCR and MAMA-PCR. Among the analyzed samples, 167 (46.13%) were positive for Campylobacter. They were detected in 38.7% (38/98) and 3% (3/98) of environment samples before and after disinfection, respectively, and in 126 (75.9%) out of 166 feces samples. In total, 78 C. jejuni and 89 C. coli isolates were identified and further studied. All isolates were resistant to macrolids, tetracycline, quinolones, and chloramphenicol. However, lower rates were observed for beta-lactams [ampicillin (62.87%), amoxicillin-clavulanic acid (47.3%)] and gentamicin (0.6%). The tet(O) and the cmeB genes were detected in 90% of resistant isolates. The blaOXA-61 gene and the specific mutations in the 23S rRNA were detected in 87% and 73.5% of isolates, respectively. The A2075G and the Thr-86-Ile mutations were detected in 85% and 73.5% of macrolide and quinolone-resistant isolates, respectively. All isolates carried the flaA, cadF, CiaB, cdtA, cdtB, and cdtC genes. The virB11, pldA, and racR genes were frequent in both C. jejuni (89%, 89%, and 90%, respectively) and C. coli (89%, 84%, and 90%). Our findings highlight the high occurrence of Campylobacter strains exhibiting antimicrobial resistance with potential virulence traits in the avian environment. Thus, the improvement of biosecurity measures in poultry farms is essential to control bacterial infection persistence and to prevent the spread of virulent and resistant strains.